2016
DOI: 10.18632/oncotarget.12609
|View full text |Cite
|
Sign up to set email alerts
|

H2S-releasing nanoemulsions: a new formulation to inhibit tumor cells proliferation and improve tissue repair

Abstract: The improvement of solubility and/or dissolution rate of poorly soluble natural compounds is an ideal strategy to make them optimal candidates as new potential drugs. Accordingly, the allyl sulfur compounds and omega-3 fatty acids are natural hydrophobic compounds that exhibit two important combined properties: cardiovascular protection and antitumor activity. Here, we have synthesized and characterized a novel formulation of diallyl disulfide (DADS) and α-linolenic acid (ALA) as protein-nanoemulsions (BAD-NEs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
40
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 149 publications
5
40
1
Order By: Relevance
“…It had been shown that H 2 S promoted the cell proliferation of human colon cancer cell (Cai, Wang, Ju, Wang, & Zhu, ), vascular endothelial cells (Papapetropoulos et al, ) and osteoblastic cell (Lv et al, ). On the contrary, H 2 S has also been reported to inhibit the cell proliferation of MCF‐7 cell (Ciocci et al, ), colon epithelial cells (Wu et al, ), and human melanoma cells (De Cicco et al, ). The complete opposite effects of H 2 S on cell proliferation might be attributed to the different cell types and culture conditions such as dose or treatment time of H 2 S. Interestingly, in our study, the results demonstrated that lower doses (< = 200 µM) of NaHS (a H 2 S donor) stimulated PMECs proliferation, while high concentration of NaHS (600 µM) inhibited PMECs proliferation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It had been shown that H 2 S promoted the cell proliferation of human colon cancer cell (Cai, Wang, Ju, Wang, & Zhu, ), vascular endothelial cells (Papapetropoulos et al, ) and osteoblastic cell (Lv et al, ). On the contrary, H 2 S has also been reported to inhibit the cell proliferation of MCF‐7 cell (Ciocci et al, ), colon epithelial cells (Wu et al, ), and human melanoma cells (De Cicco et al, ). The complete opposite effects of H 2 S on cell proliferation might be attributed to the different cell types and culture conditions such as dose or treatment time of H 2 S. Interestingly, in our study, the results demonstrated that lower doses (< = 200 µM) of NaHS (a H 2 S donor) stimulated PMECs proliferation, while high concentration of NaHS (600 µM) inhibited PMECs proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…It had been shown that H 2 S promoted the cell proliferation of human colon cancer cell (Cai, Wang, Ju, Wang, & Zhu, 2010), vascular endothelial cells (Papapetropoulos et al, 2009) and osteoblastic cell (Lv et al, 2017). On the contrary, H 2 S has also been reported to inhibit the cell proliferation of MCF-7 cell (Ciocci et al, 2016), colon epithelial cells (Wu et al, 2012) Han et al (2013) found that proliferation of lymphocytes was stimulated following treatment with NaHS at low NaHS concentrations (<1 mM) but inhibited at high NaHS concentrations (>2 mM).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent literature showed that synthetic microparticles coated with human stem cell membranes lead to the preservation of viable myocardium and augmentation of cardiac function in rodent models with MI . Similar microstructures loaded with natural bioactive compounds that generate a broad biological effect, such as linolenic acid, have shown a strong protective effect on cardiac cells . The cradle infrastructure can also be engraved with subsystems that release biological signals on‐demand .…”
Section: Supplying Cells With Proper Microenvironmental Cuesmentioning
confidence: 99%
“…The RP-HPLC analysis of the GaOS, shown in Figure 1a, indicated the presence of a main hydrophobic component (corresponding to the peaks a and b), eluted at the same retention time of DADS (see S2 Figure), which represents the major constituent (about the 60%) of the oil-garlic fraction [24]. Garlic OSCs and their conjugates have been studied as optimal H2S slow-releasing donors [23,[25][26][27]. Therefore, the ability of the GaOS solution to release H2S was here assessed by MB assay after 30 min, 2 h and 5 h of incubation at 37°C ( Figure 1B).…”
Section: Gaos Extract Production and Characterizationmentioning
confidence: 99%